A mouse mammary tumor virus mammary gland enhancer confers tissue-specific but not lactation-dependent expression in transgenic mice. - Mok, E (1992)
The long terminal repeat (LTR) of mouse mammary tumor virus (MMTV) is known to contain a number of transcriptional regulatory elements, including glucocorticoid response elements. In this study, we showed that a mammary gland/salivary gland enhancer found in the LTR of this virus directs expression of a heterologous promoter to both virgin and lactating mammary glands in transgenic mice. Using transgenic mice containing hybrid gene constructs with various deletions of the LTR sequences linked to marker genes, we also showed that the dramatic increase in MMTV expression that occurs during lactation is due to the glucocorticoid response elements. Thus, the MMTV LTR encodes two distinct elements, both of which are required for a high level of expression in lactating mammary glands.